Where are the Grown-Ups? Thinking about Anarchy with "Lord of the Flies". Issue 4 (2nd October 2021) - Mayborn, William C.
Abstract: The 1963 Peter Brook version of Sir William Golding's Lord of the Flies is a classic film that can be an instructive metaphor for International Studies and Political Science students to think about the concept of anarchy. This article explores a variety of International Relations theories by juxtaposing them with six separate themes developed by the film. After a short film synopsis and concept definition, the paper will address the following themes developed within the film: the absence of authority, the disruption of natural harmony, hegemonic power, rules and institutions, self-help and the security dilemma, and group competition. At the end of each theme, the author provides potential discussion questions on the film and the concept of anarchy.